Evaluasi Aksesibilitas Website Akademik bagi Pengguna Disabilitas Menggunakan Website Accessibility Conformance Evaluation Methodology (WCAG-EM) - Aryantoputri, Biandra; Suranto, Beni (The Indonesian Journal of Computer Science, 2025)
This study evaluates the accessibility of the academic website of Universitas Islam Indonesia (UII) using AChecker and WAVE tools based on the Web Content Accessibility Guidelines (WCAG) standards. The results indicate that most pages have potential accessibility issues, such as "use of color," "keyboard operability," and "flashing content." The WAVE tool provides more detailed insights, identifying significant issues in elements like "Non-text Content," "Contrast (Minimum)," and "Link Purpose (In Context)." Recommendations for improvement include adding alternative text, enhancing color contrast ratios, and optimizing keyboard navigation. Implementing these evaluation results is expected to improve accessibility and foster an inclusive digital environment. For further development, the study recommends direct testing by users with disabilities to ensure the effectiveness of the implemented improvements..